Primary Spinal Schwannoma: A Single Center Study Of 37 consecutively Operated Cases - Roka, Yam Bahadur; Karki, Mohan; Dahal Chettri, Arati (Nepal Journal of Neuroscience, 2022)
Primary spinal Schwannoma (PSS) remains uncommon nerve sheath tumor of the spine with male preponderance and presenting in fourth to fifth decades. They arise from the Schwann cells in sensory root as PSS or part of Neurofibromatosis 2.This is a retrospective study of histopathologically confirmed cases of PSS treated between 2010 to 2021. They were operated and age, sex, clinic-radiological findings, surgical technique used and outcome studied. Laminectomy or laminoplasty or combined anterior-posterior approach was used with either an intracapsular or extracapsular tumor removal. Follow-up was at 15 days, 2 months, 6 months and yearly intervals.There were 37 cases operated with age ranging from 16 to 81 years and majority in the 21–40-year group (40%) followed by 41 to 60 years (32%). There were 22 males and 15 females. Localized pain in the back or cervical region was the commonest finding (75%) followed by myelopathy in 38%, radiculopathy in 35% and bladder disturbances in 13%. They were most common in the lumbar region (35%) followed by thoracic (30%). With relation to the level and sex, the cervical level showed equal sex distribution while the rest had male preponderancePSS although can frequently present to the spine surgeon and the diagnosis is clinched with help of an MRI. Surgery remains the main modality of treatment either by laminectomy, laminoplasty or minimal invasive spine surgery. The nerve root of origin must be preserved in all that can be aided with help of intraoperative neurophysiological monitoring.